A cobalt-free layered oxide as an oxygen reduction catalyst for intermediate-temperature solid oxide fuel cells - Jiang, S.; Zhou, W.; Sunarso, J.; Ran, R.; Shao, Zongping (2015)
© 2015 Hydrogen Energy Publications, LLC. A cobalt-free layered oxide-Sr4Fe6O13-d is synthesized and characterized for application as a cathode of intermediate temperature solid oxide fuel cells. High temperature powder x-ray diffraction, oxygen temperature programmed desorption and electrochemical impedance spectroscopy are employed to evaluate the temperature-dependent crystal structure and oxygen reduction reaction (ORR) activity of Sr4Fe6O13-d. The oxide exhibits a single phase between room temperature and 1050 °C with low thermal expansion coefficient. The drawback of this oxide lies on its low ORR activity which is likely due to its layered structure which favors oxygen ionic transport two-dimensionally in the ac plane along the layered oxide layer. We show here that the original ORR activity can be improved by adjusting the phase compositions through an oxygen-deficient calcination process. An area specific resistance of 0.139 O cm2 at 700 °C is attained by calcining Sr4Fe6O13-d at 900 °C with ~66.2 wt% of perovskite phase in the composite material.